Rare bird documentation form for Peregrine Falcon at northeast Boone County, 1986 - Proescholdt, Bethet al (1986)
Rare bird documentation form for a Peregrine Falcon at northeast Boone County on county line with Hamilton County, IA on April 23, 1986. Epson - sheet feed